Helleristningene i Alta: Estetikken, geologien og figurene - Tansem, Karin (UiT Norges arktiske universitet, 2022)
The dissertation contains an analysis and a re-evaluation of the Alta rock engravings, where the aesthetic qualities of the rocks and the engravings constitute the point of departure. Aesthetics is this context is not conceived of as something connected to beauty or art, but rather defined simply as cognition by sensory perception, the qualities of objects that can be perceived by the senses and the very sensing itself. Three papers with quite different approaches to the Alta rock engravings have been produced: Geological features at the rock art site Jiepmaluokta were investigated, by geoarchaeologist Per Storemyr and the author. Our conclusion was that the rock engravings in Jiepmaluokta most likely were produced on rocks coated with a red ferrous film, which disappeared when the rocks where colonised by lichen. One of the four major rock art sites in Alta, Storsteinen, was re-documented and the result analysed, mainly by comparing the content with that on other rock engraving sites. Storsteinen does not fit within the established chronological phases of the Alta rock art, but rather seems to represent a segment of its own. The analysis also demonstrated that the figures’ variation within the phases and the similarities between them are substantial. In the third paper, the ways the Alta rock art has been interpretated since its discovery in the 1970s were described, and alternative approaches suggested. In the introduction, rock art as archaeological objects and how they are conceived of as not belonging to the realm of art, are discussed. The variations the figures display are presented, as is accumulative processes that may explain the large concentrations of rock art at some locations. Further, the aesthetics of the rocks and the seashore are described. The value of recognising creativity in the past and uncertainty in the present are underlined, continuing into a discussion on authenticity and democratisation connected to dissemination of the Alta rock art. Helleristningene i Alta består av tusenvis av ...